Ni/NiO/C Composites Derived from Nickel Based Metal-Organic Frameworks for Improved Enzyme-Based Biosensor. Issue 12 (8th August 2017) - Liu, Dan; Dong, Sheying; Wei, Wenbo; Fu, Yile; Huang, Tinglin
Abstract : Ni/NiO/C composites were prepared by successively thermal annealing Ni-based metal organic frameworks (Ni-MOFs) in nitrogen and air atmosphere. Moreover, comparative electrochemical properties of the material before and after calcination were investigated by electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). The result indicated that the Ni/NiO/C was more suitable for the matrix of myoglobin (Mb)/hemoglobin (Hb) immobilization to fabricate enzyme-based biosensor for the detection of nitrite (NO2 − ). Among them, the Mb-based biosensor exhibited a wider linear range from 4 to 40892 μM with a lower detection limit of 1.3 μM (S/N = 3) toward NO2 − . The good electrochemical properties of Ni/NiO/C could be mainly due to the synergistic integration of MOFs-derived Ni, NiO and carbon hybrids, which could work as electron conducting pathways between the Mb (Hb) and the electrode surface to facilitate the electron transfer process. Therefore, this work suggested that MOF-derived composites have a great potential for constructing wide range of sensing interface.